2011
DOI: 10.1039/c1cc12402a
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of mesoporous polymer monolith: a template-free approach

Abstract: Mesoporous polyacrylonitrile (PAN) monolith has been fabricated by a template-free approach using the unique affinity of PAN towards a water/dimethyl sulfoxide (DMSO) mixture. A newly developed Thermally Induced Phase Separation Technique (TIPS) has been used to obtain the polymer monoliths and their microstructures have been controlled by optimizing the concentration and cooling temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
94
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 131 publications
(96 citation statements)
references
References 30 publications
1
94
0
Order By: Relevance
“…Figure 2 shows FE-SEM images of the CNT-coated PAN monolith with different magnifications. In our previous study, 7 the nitrogen adsorption/desorption isotherms recorded on the monolith as well as the FE-SEM observations confirmed that it had both macropores and mesopores inside. The fibrous CNTs were observed to adsorb on the macropore surface of the monolith uniformly.…”
Section: Cnt-coated Monolithmentioning
confidence: 89%
See 2 more Smart Citations
“…Figure 2 shows FE-SEM images of the CNT-coated PAN monolith with different magnifications. In our previous study, 7 the nitrogen adsorption/desorption isotherms recorded on the monolith as well as the FE-SEM observations confirmed that it had both macropores and mesopores inside. The fibrous CNTs were observed to adsorb on the macropore surface of the monolith uniformly.…”
Section: Cnt-coated Monolithmentioning
confidence: 89%
“…1. 7 Both diameter and height of the columnar monolith were about 10 mm. The porosity and average pore size were ca.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have developed a new method to fabricate polymeric monoliths from the corresponding polymer solutions by thermally induced phase separation (TIPS) or non-solvent induced phase separation. These methods are very convenient to prepare monoliths with interconnected porous structure without any templates [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The resultant porous structure is disordered in shape, and it is accompanied by difficulties in the precise control of the porous structural parameters such as pore and skeleton size. Recently, we have reported the fabrication of polymer monolith by thermally induced phase separation (TIPS) [32,33]. This method is an excellent way to prepare microcellular foams and membranes with controlled morphologies.…”
mentioning
confidence: 99%